PEMBAHARUAN USHUL FIQH: STUDI PEMIKIRAN NU’MAN JAGHIEM - Hamidah, Tutik; Faozan, Ahmad (TAHKIM, 2024)
AbstractThe renewal of ushul fiqh has become one of the factual topics in the study of modern Islamic treasures. The demands of the progress of the times and the increasingly complex problems in Muslim society today require a new answer to the problems that arise. Even so, efforts to renew the discipline of Ushul Fiqh can be carried out if the public is aware of the phenomenon of stagnation of traditional fiqh, that ushul fiqh can be renewed. It is this strong will and awareness that can actually be built if people realize the need for reform of religious thought and practice it on a large scale. There have been many Muslim scholars who have proposed renewal in the discipline of ushul fiqh, which is solely for one purpose, namely; shows that religion can be used to solve everyday problems. Nu'man Djahiem, is a figure from Malaysia who deserves appreciation in the field of renewal of Ushul Fiqh. Brilliant ideas and practical solutions seem to have entered the paradigm of Indonesian Islamic thought, especially the reformation paradigm of ushul fiqh which is still stagnant.Nu'man Djaheim has the same view, regarding the reformulation of Ushul fiqh that has been produced by the previous ulama'. So that Usul fiqh can be more developed and adaptive to various new problems. Nu'man Djahiem's renewal offer, namely:i'ādah ṣiyāghatihi bi uslūb manhaji, formulating fiqh proposals as a method or tool that is always used. Second, Ar-rabṭ bayna qaḍāya 'ilm al-uṣūl wa 'ilm uṣūl al-qānūn. Linking and integrating the science of usul fiqh with the science of legislation. Third, Istifādah min 'ulūm al-'aql allati tajarradat wa taṭawwara. Making this renewal according to the character of the science of ushul fiqh is appropriate.Keyword: Ushul Fiqh, Nu’man Djaghiem, Pembaruan AbstrakPembaharuan ushul fiqh menjadi salah topik faktual dalam kajian khazanah Islam modern. Tuntutan kemajuan zaman dan semakin kompleknya persoalan ditengah masyarakat muslim dewasa ini membutuhkan sebuah jawaban baru atas persoalan yang muncul. Meskipun demikian upaya pembaharuan dalam disiplin ilmu Ushul Fiqh ini dapat dilakukan jika masyarakat menyadari fenomena stagnasi fiqh tradisional, ushul fiqh dapat diperbaharui. Kemauan kuat dan adanya kesadaran inilah yang sesungguhnya dapat dibangun jika masyarakat menyadari perlunya reformasi pemikiran keagamaan dan mempraktekkannya secara besar-besaran. Sudah banyak sarjana muslim yang mengusulkan pembaharuan dalam disiplin ilmu ushul fiqh, yang semata-mata untuk satu tujuan yaitu; menunjukkan bahwa agama dapat digunakan untuk memecahkan masalah sehari-hari. Nu’man Djahiem, adalah tokoh dari Malaysia yang patut mendapatkan apresiasi dalam bidang pembaharuan Ushul Fiqh. Ide-ide cemerlang dan solusi praktisnya tampaknya telah memasuki paradigma pemikiran Islam Indonesia, khususnya paradigma reformasi ushul fiqh yang masih stagnan.Nu’man Djaheim ini  memiliki pandangan yang sama, tentang bagaimana reformulasi Ushul fiqh yang telah dihasilkan oleh ulama’ sebelumnya. Sehingga Ushul fiqh bisa lebih berkembang dan adaptif terhadap berbagai permasalah baru. tawaran pembaharuan Nu’man Djahiem, yakni: i’ādah ṣiyāghatihi bi uslūb manhaji, memformulasikan usul fikih sebagai metode atau perangkat yang selalu digunakan. Kedua, Ar-rabṭ bayna qaḍāya ‘ilm al-uṣūl wa ‘ilm uṣūl al-qānūn. Mengaitkan dan memadukan antara ilmu usul fikih dengan ilmu perundang-undangan. Ketiga, Istifādah min ‘ulūm al-‘aql allati tajarradat wa taṭawwara . Menjadikan pembaharuan ini sesuai karakter ilmu ushul fiqh sesuai.Keyword: Ushul Fiqh, Nu’man Djaghiem, Pembaruan